Religious fictionalism. Issue 3 (22nd January 2018) - Scott, Michael; Malcolm, Finlay
Abstract: Religious fictionalism is the theory that it is morally and intellectually legitimate to affirm religious sentences and to engage in public and private religious practices, without believing the content of religious claims. This article discusses the main features of fictionalism, contrasts hermeneutic, and revolutionary kinds of fictionalism and explores possible historical and recent examples of religious fictionalism. Such examples are found in recent theories of faith, pragmatic approaches to religion, and mystical traditions in religious theology.